Understanding social problems - Mooney, Linda A.; Knox, David 1943-; Schacht, Caroline (Belmont, CA Wadsworth Cengage Learning, 2011)
Textbook for college-level sociology courses addressing social problems in the United States.
Sociology and the study of social problems -- Problems of well-being -- Problems of inequality -- Problems of globalization.
Includes bibliographical references and index.
Keywords: Social problems -- United States; United States -- Social conditions -- 1980-2020.